IMPROVING THE UNDERSTANDING CONCEPT OF LOCAL WISDOM BASED ON PROBLEM-BASED LEARNING: TEACHING MATERIALS “LENTERA” IN ELEMENTARY SCHOOL - Silvi Fatimah Azhara Suherman; Mubarok Somantri; Non Dwishiera Cahya Anasta Shiera (Universitas Islam Negeri Mataram, 2025)
This study is motivated by fourth-grade students who have difficulty understanding the concept of IPAS, especially in local wisdom material. Based on the observation of the lack of teaching materials that support learning and teacher-centred learning methods. The purpose of this research is to develop PBL-based